OPTIMIZATION APPLIED TO ENERGY EFFICIENCY AND THERMAL COMFORT OF BUILDINGS: BIBLIOMETRIC ANALYSIS ON TECHNIQUES AND APPLICATIONS - Silva, C. F. da; Freire, R. Z.; Mendes, N. (Revista de Engenharia Térmica, 2018)
The world’s energy demand has raised concerns about supply difficulties, depletion of natural resources and environmental impacts such as destruction of ozone layer, global warming, climate change, among others. Recent studies indicate that energy consumption in buildings represents more than 40% of the world’s energy consumption, with more than half of that attributed to air conditioning systems. Specific regulations and control strategies for heating, ventilation and air-conditioning (HVAC) systems should provide acceptable thermal comfort and reasonable indoor air quality. The evolution of researches in these areas can be evaluated by the organization of scientific production up to now. The objective of this study is to analyze quantitatively what was produced in terms of optimization associated to both energy savings and thermal comfort in buildings. This bibliometric analysis, based on Science Direct and IEEE Xplore databases, correlates common adopted terms to quantify how optimization, especially those associated to computational intelligence, are influencing building projects where thermal comfort and energy saving are taken into account. This research assumes a sample of 76 articles, and provided a statistical evaluation considering authors identification, and both articles and journals that were more cited by researchers in this area.